Work flexibly, travel less? The impact of telework and flextime on mobility behavior in Switzerland. (June 2022) - Wöhner, Fabienne
Abstract: There is an ongoing discussion about the impact of flexible forms of work on travel behavior. Though it is generally accepted that telework decreases distance commuted, there are mixed conclusions about the notion that non-work-related journeys could be offsetting any saved commute. This paper investigates the influence of two flexible working arrangements – namely telework and flextime – on commutes, non-work traffic, and peak-period travel in Switzerland. Using the 2015 Swiss Mobility and Transport Microcensus (MTMC), this study analyzes flexible working arrangements with respect to their effects on traffic. The results show that people who work partly from home – compared to those who never telework – do indeed commute less; however, their non-work travel increases. This rebound effect completely offsets the saved commutes, resulting in a zero impact on the total distances covered. Only people who work exclusively remotely show less total mobility compared to those who never telework. However, only a small minority of people work only from home, with most teleworkers combining working on-site with some degree of working from home. Moreover, this study finds only slight potential for relieving traffic congestion through flexible working arrangements: Whereas teleworkers are less likely to commute during evening peak periods, people working flextime are even more likely to commute during morning rush hours. Hence, the distinction between morning and evening peak periods should be taken into account in future studies. Furthermore, research on flexible working arrangements and travel behavior benefits from the consideration of both non-work travel and total travel as well as the separation of part-time from full-time telework. Highlights: Part-time teleworkers commute less than those who never telework. There is a rebound effect in non-work travel for part-time teleworkers. Overall, part-time telework does not affect the total distances traveled. Telework relieves evening rush hour commutes, but flextime promotes morning peaks.